(untitled) (PANGEEA, 2025)
In the context of a dynamic labor market, individuals need to stay competitive by constantly refining their skills and acquiring new knowledge. Choosing a professional path is the first step, and success depends on the support of the organization they are part of. The development programs offered by the company are essential for the success of both the employee and the organization. The paper titled "Perspectives on the Impact of Development Programs on Employee Performance" aims to explore multiple perspectives on development programs and analyze their impact on individual performance.